Critical Appraisal of DNA Microarrays in Psychiatric Genomics - Mirnics, Károly; Levitt, Pat; Lewis, David A. (Biological psychiatry (1969), 2006)
Transcriptome profiling using DNA microarrays are data-driven approaches with the potential to uncover unanticipated relationships between gene expression alterations and psychiatric disorders. Studies to date have yielded both convergent and divergent findings. Differences may be explained, at least in part, by the use of a variety of microarray platforms and analytical approaches. Consistent findings across studies suggest, however, that important relationships may exist between altered gene expression and genetic susceptibility to psychiatric disorders. For example, GAD67, RGS4, DTNBP1, NRG1, and GABRAB2 show expression alterations in the postmortem brain of subjects with schizophrenia, and these genes have been also implicated as putative, heritable schizophrenia susceptibility genes. Thus, we propose that for some genes, altered expression in the postmortem human brain may have a dual origin: polymorphisms in the candidate genes themselves or upstream genetic–environmental factors that converge to alter their expression level. We hypothesize that certain gene products, which function as “molecular hubs,” commonly show altered expression in psychiatric disorders and confer genetic susceptibility for one or more diseases. Microarray gene expression studies are ideally suited to reveal these putative disease-associated molecular hubs and to identify promising candidates for genetic association studies.